Maintenance of long‐term blood pressure control and vascular health by low‐dose amiloride‐based therapy in hyperaldosteronism. Issue 8 (26th July 2019) - Izzo, Joseph L.; Hong, Michael; Hussain, Tanveer; Osmond, Peter J.
Abstract: Whether aldosterone itself contributes directly to macro‐ or microcirculatory disease in man or to adverse cardiovascular outcomes is not fully known. We report our long‐term single‐practice experience in an unusual group of five patients with chronic hyperaldosteronism (HA, including three with glucocorticoid‐remediable aldosteronism, GRA) treated with low‐dose amiloride (a specific epithelial sodium channel [ENaC] blocker) 5‐10 (mean 7) mg daily for 14‐28 (mean 20) years. Except for one GRA diagnosed in infancy, all had severe resistant hypertension. In each case, BP was normalized within 1‐4 weeks after starting amiloride and office BP's remained well controlled throughout the next two decades. 24‐hour ambulatory BP monitoring with pulse wave analysis (cardiac output, vascular resistance, augmentation index, reflection magnitude), regional pulse wave velocities, pulse stiffening ratio, ankle‐brachial index, serum creatinine, estimated glomerular filtration rate, and spot urinary albumin:creatinine ratio were measured after a mean of 18 years; all of these indicators were essentially normal. Over two additional years of observation (100 patient‐years total), no cardiovascular or renal event occurred. We conclude that long‐term ENaC blockade with amiloride can normalize BP and protect macro‐ and microvascular function in patients with HA. This suggests that either (a) putative vasculopathic effects of aldosterone are mediated via ENaC or (b) aldosterone may not play a direct role in age‐dependent vasculopathic changes in humans independent of blood pressure. These findings, coupled with our literature review in both animal and human results, underscore the need for additional studies.